Temporal patterns of the introduced sponge Hymeniacidon perlevis (Montagu, 1814) in the Elkhorn Slough, California, USA - Jackson T. Hoeke; Kerstin Wasson; Amanda S. Kahn (Aquatic Invasions)
Hymeniacidon perlevis is a cosmopolitan sponge with a seasonal life cycle. We investigated seasonal and interannual dynamics of H. perlevis in Elkhorn Slough estuary, where it is an introduced species, and explored correlations between sponge cover and environmental conditions. We used sponge cover to estimate the potential effects of H. perlevis on its environment, and how those could vary across its seasonal life cycle. We found that recruitment is currently restricted to the upper estuary and while it varies annually, the frequency and density of sponge recruits have generally increased from 2007 to 2023. A seasonal life cycle was confirmed for Elkhorn Slough populations, consistent with other temperate populations of the species, with sponge cover peaking in October and declining to a minimum from March to May. Time-lagged Spearman-ranked cross-correlations suggest that sponge cover correlated with warmer temperatures and lower dissolved oxygen at all sites, with a time lag of 2–4 months. Precipitation from severe winter storms in 2023 also coincided with declines in sponge cover. Over the course of two years, we estimated that H. perlevis biomass and potential for water filtration are greatest in fall—corresponding with peak cover, and weakest to nonexistent in the spring. Understanding the seasonal and interannual dynamics of the H. perlevis population in Elkhorn Slough can inform future approaches to manage or mitigate its ecological impacts.